1977
DOI: 10.1007/bf02615100
|View full text |Cite
|
Sign up to set email alerts
|

Improved medium for clonal growth of human diploid fibroblasts at low concentrations of serum protein

Abstract: A new medium (MCDB 104) has been developed which will support clonal growth of WI-38 cells at concentrations of serum protein as low as 25 micrograms per ml (equivalent to 0.05% serum). The principal factors responsible for reduction of the protein requirement are: (a) adjustment of all nutrient concentrations in medium F12 to experimentally determined optimum values for WI-38 cells; (b) supplementation with trace elements; (c) replacement of hypoxanthine and folic acid with adenine and folinic acid; and (d) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0

Year Published

1980
1980
2005
2005

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 265 publications
(62 citation statements)
references
References 28 publications
2
60
0
Order By: Relevance
“…This organism apparently requires serum for growth ( 18), and many cultured mammalian cells require serum or serum factors for attachment or growth or both (13). One such factor, fibronectin or cold-insoluble globulin (11), apparently was not required for attachment of G. lamblia.…”
Section: Resultsmentioning
confidence: 99%
“…This organism apparently requires serum for growth ( 18), and many cultured mammalian cells require serum or serum factors for attachment or growth or both (13). One such factor, fibronectin or cold-insoluble globulin (11), apparently was not required for attachment of G. lamblia.…”
Section: Resultsmentioning
confidence: 99%
“…O'Farrel et al (26) reported that 3T3 cells have a dual requirement for B12 and Hyp, whereas 3T6 cells require B12 alone. The folate or folinate requirement is related to the concentrations of adenine, dThd and glycine (22). B12 and folinate are reported to be essential when dThd or Hyp are absent (28).…”
Section: Discussionmentioning
confidence: 99%
“…Medium MCDB 107 (23) contains 1 nM folinic acid, which facilitates the study of the effect of extracellular purines, pyrimidines, glycine, and serine (Fig. 7) on multiplication rate (20,27). t "Lipids" refer to the class I status of purified soybean phosphatidylcholine introduced in the form of vesicles or liposomes prepared by sonication (28 [S]" is the range of concentrations of individual nutrient added to deficient medium to determine the S0.50 for multiplication at different levels of FBSP between 100 and 1000 ug/ml.…”
Section: Discussionmentioning
confidence: 99%
“…Clonal multiplication was estimated by densitometric measurement of the size of colonies formed from single cells as described (4,(20)(21)(22)(23) (vol/vol) perchloric acid at 100'C. Pyruvic acid and other 2-oxocarboxylic acids were assayed as described (25).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation